1997
DOI: 10.1046/j.1365-2249.1997.4011298.x
|View full text |Cite
|
Sign up to set email alerts
|

The priming action of tumour necrosis factor-alpha (TNF-α) and granulocyte-macrophage colony-stimulating factor (GM-CSF) on neutrophils activated by inflammatory microcrystals

Abstract: SUMMARYWe studied the effects of TNF-a or GM-CSF on the production of reactive oxygen species (as measured by chemiluminescence) and degranulation responses of neutrophils to opsonized inflammatory microcrystals. TNF-a in the 10-2000 pM or GM-CSF in the 2-200 pM concentration range caused the concentration-dependent amplification of neutrophil chemiluminescence responses to both calcium pyrophosphate dihydrate (CPPD) and monosodium urate monohydrate (MSUM) crystals. Degranulation responses, as measured by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Previous reports have already indicated and we confirmed that CPPD crystals stimulate a robust respiratory burst in human neutrophils (Fig. 4A-C) (24,49). To our surprise, we found that DPI had no significant effect on CPPD crystal-triggered extracellular DNA release in our hands (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Previous reports have already indicated and we confirmed that CPPD crystals stimulate a robust respiratory burst in human neutrophils (Fig. 4A-C) (24,49). To our surprise, we found that DPI had no significant effect on CPPD crystal-triggered extracellular DNA release in our hands (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…This response is quick, faster than that observed with the maximal NET inducer, protein kinase C activator PMA (increase in PMA-stimulated extracellular DNA levels appears 60-90 min after stimulation) (35). The CPPD crystal dose range (0-250 mg/ml) used in our work is lower than the ones used in previous CPPD-neutrophil studies (10,24,25,49). MSU crystals were shown to induce NETs in this exact same range (26,27).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The incidence of CPPD deposition in joints is estimated to be 3.6 % of the population [1]. Crystals deposited in the synovium become opsonized with proteins from the synovial fluid, and interact with various synovial cells leading to the release of chemotactic factors [2].…”
Section: Introductionmentioning
confidence: 99%